Program For Implementing Samsat Enrekang Motor Vehicle Tax Breaking Program For Taxpayers - Andi Arifwangsa Adiningrat; Nurhikmah Nurhikmah; Muhammad Khaedar Sahib; Andi Jam'an (Jurnal Riset Perpajakan: Amnesty, 2023)
The purpose of this study is to find out the optimization of the motor vehicle tax bleaching program in increasing taxpayer compliance in paying taxes at the Samsat Enrekaang office. The research object of this Final Project is "Efforts to increase awareness of taxpayers in paying taxes and paying more attention to the time of payment so as not to be fined". The data analysis technique used is applied quantitative techniques using the method of data collection, data reduction, data presentation and conclusion. The results of this study indicate that the existence of the Motor Vehicle Tax Bleaching program also increases public awareness in paying motorized vehicle taxes in Enrekang Regency. This Tax Bleaching Program also increases Local Own Revenue in the motor vehicle tax sector until the targets set are achieved.